Customer-based brand equity and customer engagement in experiential services: insights from an emerging economy - Cambra Fierro, Jesús Juan (2021)
The aim of this research is to analyze links between customer-based brand equity and customer engagement in the field of experiential services (e.g., private health clinics)—taking an emerging economy context as our reference. The authors put forth a chain of effects—based in Social Capital Theory—to test the impact of customer-based brand equity on customer engagement, mediated by satisfaction and customer reputation. Causal model estimation results suggest that customer-based brand equity has both a direct, positive impact on customer satisfaction and customer reputation and an indirect impact on customer engagement. The final section of the paper presents theoretical discussion of the results and the main implications for business practice.